Investigation into effects of tocilizumab and epoetin beta in rats with experimental sciatic nerve injury model - Kanter, Aysun Guler; Ulger, Harun; Bozkurt, Ahmet Sarper; Tarakcioglu, Mehmet; Ulusal, Hasan; Ozercan, Ibrahim Hanefi (Churchill Livingstone, 2024)
Objective: To investigate the effects of tocilizumab (TCZ), epoetin beta (EPO), and their combination on nerve regeneration in a sciatic nerve injury model. Materials and method: Male Sprague-Dawley rats were divided into (-) negative control, sham, TCZ, EPO ((+) positive control), and TCZ+EPO groups. The TCZ group received TCZ (8 mg/kg intraperitoneal) immediately after surgery. On day 14th, the EPO group received EPO (5000 IU/kg, intraperitoneal); the TCZ+EPO group received TCZ (8 mg/kg, intraperitoneal), EPO (5000 IU/kg, intraperitoneal), and TCZ (8 mg/kg, intraperitoneal) post-surgery. Motor and sensory functions were assessed pre and post-surgery. Lipid peroxidation and oxidative stress parameters were evaluated biochemically in the serum, and sciatic nerve tissue was evaluated histopathologically using haematoxylin-Eosin and Masson trichrome staining. Conclusions: TCZ and EPO decreased nerve injury effects by increasing motor and sensory conduction velocities of the sciatic nerve. Biochemically, TCZ and EPO significantly increased Superoxide Dismutase, Catalase, and Glutathione peroxidase 4 levels while decreasing Lipid Peroxidation levels (p=0.001). Histopathologically, neuronal degeneration following nerve injury was decreased in the groups receiving TCZ and EPO (p=0.001). EPO and TCZ attenuate the adverse effects of nerve injury. However, the TCZ+EPO treatment favoured biochemical activities over tissue and functional activities. This has been confirmed functionally, biochemically, and histopathologically.
Keywords: Nerve; Injury; Tocilizumab (TCZ); Epoetin beta (EPO)